Marketing Strategies of Sharia Peer-to-Peer Lending Fintech in Enhancing Sharia Financial Inclusion: A Case Study of PT. Dana Syariah Indonesia - Fuadi Tanjung, Ahmad; Sugianto, Sugianto; Syahriza, Rahmi (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to analyze the marketing strategies employed by PT. Dana Syariah Indonesia in enhancing Sharia financial inclusion through Sharia peer-to-peer lending fintech. The research uses SWOT and QSPM analyses to evaluate the company's strengths, weaknesses, opportunities, and threats in its marketing strategies. The findings reveal that the company has successfully increased access to Sharia financial services by utilizing digital media, offline events, and advanced technology. Despite challenges such as customer complaint management and digital adoption barriers, the company leverages market opportunities sensitive to riba and strengthens its position through solutions aligned with Sharia values. The study concludes that effective marketing strategies play a crucial role in expanding Sharia financial inclusion in Indonesia.